2013
DOI: 10.1002/hep.26644
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of liver disease progression in the German hepatitis C virus (1b)-contaminated anti-D cohort at 35 years after infection

Abstract: The natural course of HCV infection remains controversial. The German HCV (1b)-contaminated anti-D cohort provides an ideal population to investigate the natural course of HCV infection in a large, homogenous cohort of young women from the date of HCV inoculation. Our previous follow-up studies at 20 and 25 years after infection suggested slow fibrosis progression rates in this unique cohort. The aim of our prospective, community-based, multicenter study was to reevaluate the liver disease progression in 718 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
64
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(70 citation statements)
references
References 25 publications
2
64
0
4
Order By: Relevance
“…In historical cohorts, where the main route of hepatitis C transmission was iatrogenic rather than Intravenous drug use, alcohol use disorders and coinfections were low and liver disease progression rates remained low over decades. 5,6 All cost-effectiveness models in hepatitis C involve a reduction of liver deaths with increasing efficacy and uptake of hepatitis C treatments. 7 However, there are potential confounders such as alcohol use disorders and comorbidities, neither of which are taken into account in these models.…”
mentioning
confidence: 99%
“…In historical cohorts, where the main route of hepatitis C transmission was iatrogenic rather than Intravenous drug use, alcohol use disorders and coinfections were low and liver disease progression rates remained low over decades. 5,6 All cost-effectiveness models in hepatitis C involve a reduction of liver deaths with increasing efficacy and uptake of hepatitis C treatments. 7 However, there are potential confounders such as alcohol use disorders and comorbidities, neither of which are taken into account in these models.…”
mentioning
confidence: 99%
“…3 Poly-unsaturated fatty acids, and polyphenols such as silymarin, curcumin and resveratrol have been studied in pre-clinical models and small-scale trials demonstrating reduction in markers of liver injury, inflammation, apoptosis and oxidation. 4 In a recent issue of the journal, Loffredo et al 5 have investigated the effects of dark chocolate consumption in patients with NASH. Chocolate consumption, especially dark chocolate is associated with lowering of lipid peroxidation and thereby improving cardiovascular risk.…”
Section: Acknowledgementmentioning
confidence: 99%
“…Indeed, several cohort studies in hepatitis C infected individuals demonstrated that in the absence of risk factors (such as alcohol consumption), progression to severe liver disease may take decades or may not occur at all in the vast majority of patients. 3,4 One problem for a substantial group of patients with chronic hepatitis C is impaired quality of life (QoL). 5 Patients with advanced fibrosis have impairment in quality of life.…”
mentioning
confidence: 99%
“…The presence of hepatocyte death, reflected by increased of serum alanine amino transferase (ALT) and aspartate amino transferase (AST), is a widely used marker to screen and monitor patients with liver disorders. Moreover, these markers drive therapeutic decisions; have prognostic value for patients with hepatitis B virus (HBV) (Lok 2004;Lazo et al 2011;Cui et al 2013;Rehm et al 2013), and hepatitis C virus (HCV) (Wiese et al 2000;Ghany et al 2003;Hui et al 2003;Wiese et al 2014). There were also no reports on the combination of liver lobe volume with albumin to determine the presence of esophageal varices in cirrhotic patients (Ranjith et al 2003;Wiese et al 2014).…”
Section: Introductionmentioning
confidence: 99%